The Dlt and LiaFSR systems derepress SpeB production independently in the Δpde2 mutant of Streptococcus pyogenes - Faozia, Sabrina; Hossain, Tasmim; Cho, Kyu Hong (Frontiers in Cellular and Infection Microbiology, 2023)
The second messenger molecule, c-di-AMP, plays a critical role in pathogenesis and virulence in S. pyogenes. We previously reported that deleting the c-di-AMP phosphodiesterase gene pde2 severely suppresses SpeB production at the transcriptional level. We performed transposon mutagenesis to gain insight into the mechanism of how Pde2 is involved in SpeB regulation. We identified one of the genes of the dlt operon, dltX, as a suppressor of the SpeB-null phenotype of the ∆pde2 mutant. The dlt operon consists of five genes, dltX, dltA, dltB, dltC, and dltD in many Gram-positive bacteria, and its function is to incorporate D-alanine into lipoteichoic acids. DltX, a small membrane protein, is a newly identified member of the operon. The in-frame deletion of dltX or insertional inactivation of dltA in the ∆pde2 mutant restored SpeB production, indicating that D-alanylation is crucial for the suppressor phenotype. These mutations did not affect the growth in lab media but showed increased negative cell surface charge and enhanced sensitivity to polymyxin B. Considering that dlt mutations change cell surface charge and sensitivity to cationic antimicrobial peptides, we examined the LiaFSR system that senses and responds to cell envelope stress. The ∆liaR mutation in the ∆pde2 mutant also derepressed SpeB production, like the ∆dltX mutation. LiaFSR controls speB expression by regulating the expression of the transcriptional regulator SpxA2. However, the Dlt system did not regulate spxA2 expression. The SpeB phenotype of the ∆pde2∆dltX mutant in higher salt media differed from that of the ∆pde2∆liaR mutant, suggesting a unique pathway for the Dlt system in SpeB production, possibly related to ion transport or turgor pressure regulation.